Body growth of North Atlantic right whales ( Eubalaena glacialis ) revisited - Sarah M. E. Fortune; Michael J. Moore; Wayne L. Perryman; Andrew W. Trites (Marine Mammal Science, 2021)
Knowing size‐at‐age is important for determining food requirements and making inferences about the nutritional status of individuals and their populations. Accurate growth curves are also needed to quantify drug dosages to treat wounded or entangled animals. However, body sizes are often based on small numbers of measured animals that must be improved as new data become available. We updated an existing body growth model for North Atlantic right whales (NARWs) using new data from dead animals and from older individuals. Our models indicate that NARWs attain mean lengths and weights of 4.3 m and 1.0 mt at birth, and 13.1 m and 31.7 mt when sexually mature. Calves more than double their length and attain nearly three‐quarters of their asymptotic adult size during their first year of life. Overall, our length estimates agreed well with previous estimates, but our mass‐at‐age values were considerably higher. These differences revealed that necropsy data used alone in allometric models underestimate mass due possibly to several of the stranded animals in the database having been chronically entangled and in poor body condition. Augmenting the database with healthier individuals, such as harvested North Pacific right whales, yielded mass predictions that reflect both healthy and unhealthy individuals.

Environmental factors influencing eastern North Pacific gray whale calf production 1994–2016 - Wayne L. Perryman; Trevor Joyce; David W. Weller; John W. Durban (Marine Mammal Science, 2021)
This paper describes the relationship between eastern North Pacific gray whale calf production and environmental conditions in the Pacific Arctic where they feed. The results show how interannual variation in sea ice cover in the Bering and Chukchi Seas along with broader indices of North Pacific climate, such as Pacific Decadal Oscillation (PDO) and North Pacific Index (NPI), are linked to variation in gray whale reproductive output. Estimates of gray whale calf production were derived from 23 consecutive years (1994–2016) of shore‐based visual surveys conducted off California during the northward migration. PDO and NPI in combination with ice cover in the Bering and Chukchi Seas during the early phase of gestation appear to be important in explaining the observed variability in calf production. Of the 2,285 time series linear models evaluated, the model of best‐fit included PDO(July), Ice(June), NPI(February), and explained 60% of the observed variability in calf production. After elimination of two data outliers in calf production estimates (2013 and 2014) a model including Ice(May), PDO(May), and NPI(July) explained 90% of the variability. We conclude that access to prey early in the gestation period is critical to reproductive success in this population and may be important for other capital breeding mammals.

Drones Minimize Antarctic Predator Responses Relative to Ground Survey Methods: An Appeal for Context in Policy Advice - Douglas J. Krause; Jefferson T. Hinke; Michael E. Goebel; Wayne L. Perryman (Frontiers in Marine Science, 2021)
Unoccupied aerial systems (UAS) have become common tools for ecological monitoring and management. However, UAS use has the potential to negatively affect wildlife. Both policy makers and practitioners require data about the potential impacts of UAS on natural biota, but few studies exist and some of the published results conflict. We conducted two experiments to assess the responses of chinstrap penguins ( Pygoscelis antarcticus ), Antarctic fur seals ( Arctocephalus gazella ), and leopard seals ( Hydrurga leptonyx ) to UAS overflights. First, to provide a baseline for assessing disturbance from UAS operations, we compare behavioral responses from UAS flights to those from traditional, ground surveys. Second, to inform users and policy makers about preferred flight methods, we assess behavioral and physiological responses to UAS flown at specific altitudes, during different stages of breeding chronology, and with other site factors. Between January 2017 and March 2018 we conducted 268 UAS flight approaches and 36 ground-based surveys at Cape Shirreff, Antarctic Peninsula. We applied generalized linear mixed effects models and Kruskal-Wallis tests to 10,164 behavioral scores obtained from three independent observers. When directly compared, behavioral responses by all species to UAS overflights at 30 m were not different from control periods, while responses to ground surveys were significantly more intense. Behavioral responses generally increased as UAS flew lower, and for penguins those increases intensified as the breeding season progressed (i.e., guard and molt stages). We argue that results from UAS wildlife response studies need to be assessed relative to the impacts of alternative methods, and within the ecological context of the target species. Finally, we suggest data-driven best practices for both UAS use and for the design of future UAS-wildlife response studies.

Accuracy and precision of dolphin group size estimates - Tim Gerrodette; Wayne L. Perryman; Cornelia S. Oedekoven (Marine Mammal Science, 2019)
Estimating the number of dolphins in a group is a challenging task. To assess the accuracy and precision of dolphin group size estimates, observer estimates were compared to counts from large‐format vertical aerial photographs. During 11 research cruises, a total of 2,435 size estimates of 434 groups were made by 59 observers. Observer estimates were modeled as a function of the photo count in a hierarchical Bayesian framework. Accuracy varied widely among observers, and somewhat less widely among dolphin species. Most observers tended to underestimate, and the tendency increased with group size. Groups of 25, 50, 100, and 500 were underestimated by

Reproduction and morphology of Central American and Tres Marias spinner dolphins in the eastern tropical Pacific - Susan J. Chivers; Wayne L. Perryman; Morgan S. Lynn (Marine Mammal Science, 2019)
Four geographic forms of spinner dolphin ( Stenella longirostris ) occur in the eastern tropical Pacific. Two of the forms are pelagic: the eastern and whitebelly, and two are coastal: the Central American and Tres Marias spinner dolphins. Of these, only the Tres Marias form lacks recognition appropriate for developing management and conservation plans. Vertical aerial photographs of 57 spinner dolphin schools taken between 1988 and 2006 were used to examine the range of coastal forms and to characterize their calving seasons. On the basis of adult body length, spinner dolphins photographed off Guerrero, Mexico, were identified as those of the Central American form, which is north of their known range, and those photographed farther north, approximately 112 km off Nayarit, Mexico, were identified as the Tres Marias form. Calving peaked from October through March, and there was evidence that calving seasons differed among geographic forms with coastal forms calving later than pelagic forms. We present the first life history parameter estimates for the coastal forms of spinner dolphins, provide additional support for recognition of the Tres Marias form, and the first evidence of the Central American form occurring north of the Gulf of Tehuantepec, Mexico.

Photogrammetry of blue whales with an unmanned hexacopter - John W. Durban; Michael J. Moore; Gustavo Chiang; Leigh S. Hickmott; Alessandro Bocconcelli; Gloria Howes; Paulina A. Bahamonde; Wayne L. Perryman; Donald J. LeRoi (Marine Mammal Science, 2016)

Comparison of reproductive parameters for populations of eastern North Pacific common dolphins: Delphinus capensis and D. delphis - Susan J. Chivers; Wayne L. Perryman; Morgan S. Lynn; Tim Gerrodette; Frederick I. Archer; Kerri Danil; Michelle Berman‐Kowalewski; James P. Dines (Marine Mammal Science, 2016)
Reproductive parameters were estimated and compared for eastern North Pacific populations of common dolphins using specimen and photogrammetric data. Age and length data for Delphinus capensis and D. delphis specimens recovered as bycatch or strandings were used to estimate the postnatal growth rates needed to estimate age for calves measured in aerial photographs. Bayesian methods propagated uncertainty among models and revealed that the 2009 cohort of calves had birth dates centered on 6 March 2009 for D. capensis and 12 December 2008 for D. delphis . The evidence for discrete calving seasons suggests a mechanism of reproductive isolation has evolved between species. Photogrammetric data and Bayesian methods were also used to estimate the average length at which calves swim independently: 145.1 cm (≈ 11.1 mo) in D. capensis and 140.1 cm (≈ 14.0 mo) in D. delphis , and the proportion of calves (calves/dolphins counted): 0.045 in D. capensis and 0.069 in D. delphis . The latter parameter was converted to an index of calf production (calf/female dolphin) that was >50% lower than pregnancy rates suggesting few births occurred during the study year. Comparisons of regional differences in calf production suggest variability in habitat use patterns within the study area.

A small unmanned aerial system for estimating abundance and size of Antarctic predators - Michael E. Goebel; Wayne L. Perryman; Jefferson T. Hinke; Douglas J. Krause; Nancy A. Hann; Steve Gardner; Donald J. LeRoi (Polar Biology, 2015)

Are there biases in biopsy sampling? Potential drivers of sex ratio in projectile biopsy samples from two small delphinids - Nicholas M. Kellar; Marisa L. Trego; Susan J. Chivers; Fredrick I. Archer; Jeremiah J. Minich; Wayne L. Perryman (Marine Mammal Science, 2013)
Molecular assays were used to determine the sex of 1,294 biopsied common dolphins (658 long‐beaked common dolphins, Delphinus capensis , and 636 short‐beaked common dolphins, D. delphis ) in the Southern California Bight. Sex ratio differed substantially between the two species; females comprised 241 (36.6%) of D. capensis samples and 410 (64.5%) of D. delphis samples. All biopsies were taken either from a large research ship or from a small, rigid‐hull inflatable boat ( RHIB ) launched from the larger ship. When conducting replicate biopsy effort on the same schools from each vessel/platform (“Tandem Biopsy Sampling”), we found evidence that disproportionately more female D. capensis were biopsied from the RHIB than from the ship but the same was not true for D. delphis . We suspect that these results are driven by bowriding‐behavior differences between the two species. Biopsy duration, geographic location, school size, and Julian date were considered as potential covariates with sex ratio; geographic location was the only one to show strong evidence of correlation. This study also presents an alternative to the erroneous practice of comparing sex ratios to a theoretical assumption of parity ( i.e ., 50:50 sex ratio) when researchers avoid sampling animals paired with calves.

GRAY WHALE CALF PRODUCTION 1994–2000: ARE OBSERVED FLUCTUATIONS RELATED TO CHANGES IN SEASONAL ICE COVER? - Wayne L. Perryman; Meghan A. Donahue; Peter C. Perkins; Stephen B. Reilly (Marine Mammal Science, 2002)
A bstract We conducted shore‐based sighting surveys to estimate the number of northbound migrating gray whale calves passing Piedras Blancas, California, for seven consecutive years (1994–2000). In addition, we conducted aerial surveys to determine offshore distribution of the migration in 1994 and 1995, measured day/night migration rates with thermal sensors in 1994–1996, and maintained concurrent replicate watches near the peak of each migration to estimate the proportion of the cow/calf pairs missed by the standard watch team. During good weather, we counted 325, 194, 407, 501, 440, 141, and 96 calves during 1994–2000, respectively. Correcting these counts for periods not on watch and for calves missed, produced final estimates of 945 calves (SE = 68.21) for 1994, 619 calves (SE = 67.19) for 1995, 1,146 calves (SE = 70.67) for 1996, 1,431 calves (SE = 82.02) for 1997, 1,388 calves (SE = 91.84) for 1998, 427 calves (SE = 41.10) for 1999, and 279 calves (SE = 34.79) for 2000. Calf production indices (calf estimate/total population estimate) are 4.2%, 2.7%, 4.8%, 5.8%, 5.5%, 1.7%, and 1.1% for the years 1994–2000, respectively. Fluctuations in calf production over this time period were positively correlated with the length of time that primary feeding habitat was free of seasonal ice during the previous year.

ARE GRAY WHALES HITTING “K” HARD? - Sue E. Moore; Jorge Urbán R.; Wayne L. Perryman; Frances Gulland; Hector Perez‐Cortes M.; Paul R. Wade; Lorenzo Rojas‐Bracho; Teri Rowles (Marine Mammal Science, 2001)

COUNTING STELLER SEA LION PUPS IN ALASKA: AN EVALUATION OF MEDIUMFORMAT, COLOR AERIAL PHOTOGRAPHY - Gary M. Snyder; Kenneth W. Pitcher; Wayne L. Perryman; Morgan S. Lynn (Marine Mammal Science, 2001)
A bstract Estimates of Steller sea lion ( Eumetopias jubatus ) pup production are valuable for estimating population trend and size. Currently in Alaska, pups are counted by visiting rookeries, driving older animals into the water, then walking through the rookeries and counting the pups, a highly disruptive procedure. At smaller rookeries, with good vantage points, pups are occasionally counted from the periphery of rookeries without disturbing the sea lions. We evaluated counts made from medium‐format, color, aerial photographs as an alternative to drive counts and peripheral counts. Neither the peripheral counts nor the aerial photographic counts disturbed animals on the rokeries. There were strong 1:1 linear relationships between photographic counts and drive counts ( r 2 = 0.966, P r 2 = 0.999, P

DIEL VARIATION IN MIGRATION RATES OF EASTERN PACIFIC GRAY WHALES MEASURED WITH THERMAL IMAGING SENSORS - Wayne L. Perryman; Meghan A. Donahue; Jeffrey L. Laake; Thomas E. Martin (Marine Mammal Science, 1999)
A bstract We recorded the blows of gray whales during their southbound migration past central California in January 1994, 1995, and 1996, using thermal imaging sensors. For our sampling purposes, we defined day (0730–1630) and night (1630–0730) to coincide with the on/off effort periods of the visual counts being conducted concurrently. We pooled data across the three years of sampling and tested for diel variation in surfacing interval, pod size, offshore distance, migration rate, and swimming speed by comparing paired day/night means for samples collected within the respective 24‐h period. We performed these tests using data from the entire migration period and then repeated the tests for samples collected prior to and after the approximate median migration date (15 January). Over the entire migration period we observed larger diurnal pod sizes (x̄ day = 1.75 ± 0.280, x̄ night = 1.63 ± 0.232) and greater diurnal offshore distances (x̄ day = 2.30 ± 0.328 km, x̄ night = 2.03 ± 0.356 km) but found no diel variation in surfacing interval. For the entire migration period, the nocturnal migration rate (average number of whales passing per hour) was higher than the diurnal rate. During the first half of the migration we detected no diel variation in pod size or surfacing interval, but diurnal offshore distances were larger than at night (x̄ day = 2.28 ± 0.273 km, x̄ night = 1.96 ± 0.318 km). Diurnal and nocturnal migration rates prior to 15 January were not different. During the second half of the migration, there was no diel variation in surfacing interval, pod size, or distance offshore, but the nocturnal migration rate was higher (28%, SE = 11.6%) than the diurnal rate. We found no diel variation in swimming speed in any comparison. We propose that later migrants socialize more during the day, which effectively slows their diurnal rate of migration relative to nocturnal rates.

A NEW GEOGRAPHIC FORM OF THE SPINNER DOLPHIN, STENELLA LONGIROSTRIS , DETECTED WITH AERIAL PHOTOGRAMMETRY - Wayne L. Perryman; Robin L. Westlake (Marine Mammal Science, 1998)
A bstract Analyses of skeletal and external morphology of spinner dolphins killed in to the yellowfin tuna purse‐seine fishery in the eastern tropical Pacific led to the description of two subspecies of spinners from this region, the eastern spinnen dolphin and the Central American spinner dolphin (Perrin 1990). However, when we examined lengths of spinner dolphins taken from vertical aerial photographs from the same area, we found three unique morphotypes. Two of these forms correspond, at least in average length and distribution, to the existing subspecies. The third form is intermediate in length between the two recognized subspecies and is found along the edge of the continental shelf north of Cabo Corrientes, Mexico. We provisionally call this form the “Tres Marias spinner dolphin.” Our results demonstrate the value of a mix of fishery and fishery‐independent data in studies of stock structure of impacted species.